2020
DOI: 10.3390/ncrna6030025
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAs in Non-Small-Cell Lung Cancer

Abstract: Lung cancer is associated with a high mortality, with around 1.8 million deaths worldwide in 2018. Non-small-cell lung cancer (NSCLC) accounts for around 85% of cases and, despite improvement in the management of NSCLC, most patients are diagnosed at advanced stage and the five-year survival remains around 15%. This highlights a need to identify novel ways to treat the disease to reduce the burden of NSCLC. Long non-coding RNAs (lncRNAs) are non-coding RNA molecules longer than 200 nucleotides in lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 138 publications
(218 reference statements)
0
54
0
3
Order By: Relevance
“…They do not have an open reading frame, often harbor a poly-A tail, can be spliced, and are generally found in the cytoplasm and nucleus of a cell [46,65,67,68]. LncRNAs found in the nucleus are functionally involved in gene regulatory procedures, such as promoter specific repression or activation of transcription [34,[69][70][71] or epigenetic gene regulation [72,73] and those found in the cytoplasm modulate post-transcriptional gene regulatory processes [7,37,46,[74][75][76]. In addition, they modulate protein interactions, stability and affect their cellular localisation, together with controlling signalling cascades and any changes in gene expression [73].…”
Section: Overview Of Ncrnasmentioning
confidence: 99%
See 2 more Smart Citations
“…They do not have an open reading frame, often harbor a poly-A tail, can be spliced, and are generally found in the cytoplasm and nucleus of a cell [46,65,67,68]. LncRNAs found in the nucleus are functionally involved in gene regulatory procedures, such as promoter specific repression or activation of transcription [34,[69][70][71] or epigenetic gene regulation [72,73] and those found in the cytoplasm modulate post-transcriptional gene regulatory processes [7,37,46,[74][75][76]. In addition, they modulate protein interactions, stability and affect their cellular localisation, together with controlling signalling cascades and any changes in gene expression [73].…”
Section: Overview Of Ncrnasmentioning
confidence: 99%
“…LncRNAs found in the nucleus are functionally involved in gene regulatory procedures, such as promoter specific repression or activation of transcription [34,[69][70][71] or epigenetic gene regulation [72,73] and those found in the cytoplasm modulate post-transcriptional gene regulatory processes [7,37,46,[74][75][76]. In addition, they modulate protein interactions, stability and affect their cellular localisation, together with controlling signalling cascades and any changes in gene expression [73]. CircRNAs are a category of endogenous ncRNA molecules which are widely expressed in eukaryotic cells and exhibit both location-and step-specificity [77,78].…”
Section: Overview Of Ncrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Current research suggests that the functional mechanism of lncRNA mainly includes the regulation of transcription, post-transcriptional regulation, protein transport and mRNA degradation. 8,9 Many studies have shown that lncRNAs can act as either tumor suppressors or promoters in the occurrence and development of NSCLC, such as PCNA-AS1 and FTX. 10,11 LncRNA HLA complex group 11 (HCG11) has been reported to be involved in human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, lncRNAs regulate a broad range of biological processes, including aging, cell growth and differentiation, hematopoiesis, and immune response [ 8 , 9 , 10 , 11 ]. Accordingly, numerous studies have reported highly diverse roles for lncRNAs in cancer [ 12 , 13 , 14 ], including development and maintenance of resistance to anti-cancer therapy [ 15 , 16 , 17 , 18 ]. Most prominent examples involve well-characterized lncRNAs, such as CDKN2B antisense RNA 1 ( CDKN2B-AS1 , also known as ANRIL ) [ 19 ], growth arrest specific 5 ( GAS5 ) [ 20 , 21 ], H19 imprinted maternally expressed transcript ( H19 ) [ 22 , 23 ], HOX transcript antisense RNA ( HOTAIR ) [ 24 , 25 ], metastasis associated lung adenocarcinoma transcript 1 ( MALAT1 ) [ 26 , 27 ], and X inactive specific transcript ( XIST ) [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%